Atmospheric Ice Nucleating Particle measurements at the high mountain observatory Mt. Cimone (2165 m a.s.l., Italy). (December 2017) - Rinaldi, M.; Santachiara, G.; Nicosia, A.; Piazza, M.; Decesari, S.; Gilardoni, S.; Paglione, M.; Cristofanelli, P.; Marinoni, A.; Bonasoni, P.; Belosi, F.
Abstract: Measurement campaigns at the high mountain Observatory Mt. Cimone (CMN; 2165 m a.s.l.) were performed during May 2014 and October 2015. The concentration of Ice Nucleating Particles (INPs) were measured offline with a dynamic filter processing chamber (DFPC), in the deposition and condensation mode, after collecting PM1 and PM10 aerosol samples. Presented INP data are the first ever published for a high mountain site in the Mediterranean basin. During the May campaign, parallel INP measurements were also carried out at San Pietro Capofiume (SPC), a low altitude rural background area within the Po Valley basin, by the same offline technique. The average INPPM10 concentration at CMN was 86 m −3 (saturation ratio Sw = 1.01; T = −18 °C) during the May 2014 campaign, while it was 171 m −3 at SPC, in the same period. A lower average INPPM10 concentration was observed at CMN during October 2015 (43 m −3 ). A significantly higher activated fraction (AF) characterized the October 2015 campaign, suggesting that the seasonal changes in the aerosol sources have an impact on the INP efficiency of the aerosol at CMN. Super-micrometer INP contributed for ∼30% of total INP in the May 2014 campaign, at both sites, and for ∼70% in the October 2015 campaign, showing the importance of coarse particles in the INP population. The analysis of meteorological parameters, gaseous tracers concentrations and backwards trajectories suggests that the INP population at CMN is contributed by transport processes occurring at diverse spatial scales, from the local to the synoptic scale. During the Saharan Dust transport Event observed in May 2014, a reduction of the AF was observed, suggesting, for this case, a limited ice nucleating activity for Saharan dust particles. This may be due to physico-chemical aging of the Saharan dust particles during transport or to the relatively high activation temperature at which the experiments were performed in this study. Highlights: We present the first INP data for a high mountain site in the Mediterranean Basin. Average INP concentration at the mountain site is half than at sea level. Reduced INP efficiency was observed during a Saharan dust event. Transport processes at diverse spatial scales contribute to INP population. Values of INP concentrations evidence the high contribution of coarse particles.